(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2024)
This paper investigates the complex relationship between family dynamics and societal influences in Ikechukwu Ezema’s poignant novel, The Reward. Despite the paucity of research examining these concepts within the text, family and society are intricately linked and hold deep sociological significance. Through a meticulous analysis of the novel’s narrative, this study explores how human actions and behaviour shape the contours of familial relationships and their reverberating impact on the broader societal fabric. By scrutinizing the events and scenarios depicted in The Reward, this paper illuminates the ways in which parenting, upbringing, and familial bonds mold individuals, ultimately influencing their roles and contributions to society. The study offers a nuanced examination of The Reward, unveiling the multifaceted interaction between the microcosm of family and the macrocosm of society. It delves into the complexities of human behaviour, parental influence, and the intricate web of familial dynamics, shedding light on their profound impact on individual development and societal structures. Through a comprehensive analysis, this paper unravels the profound truths woven into Ezema’s narrative, accentuating the long-term significance of these sociological concepts in shaping the human experience.